Pengaruh Game Simulasi sebagai Suplemen Pembelajaran terhadap Motivasi dan Hasil Belajar Siswa SMK Kuliner - Tambunan, Alisha Nismara Kalish; Miranti, Mauren Gita; Handajani, Sri; Bahar, Asrul (Yayasan Amanah Nur Aman, 2025)
This study aims to analyze the effect of implementing simulation game on students’ motivation and learning outcomes as a more interactive and effective learning approach. This quantitative study employed a One-Group Pre-test Post-test experimental design and correlation design with 17 students from the 11th grade culinary class as the subjects. The instruments consisted of motivation questionnaires and learning outcome tests, analyzed using paired-sample t-test, pearson product moment correlation, and MANOVA. The results indicate that the application of simulation games significantly influenced motivation levels (Cohen’s d = 0,96) and learning outcomes (Cohen’s d = 0,52). MANOVA analysis revealed a strong simultaneous effect (η² = 0,848), although the correlation between motivation and learning outcomes was not statistically significant (r = 0,452; p > 0,05). It is recommended that simulation games be used continuously as an innovative learning medium, and that further studies be conducted over multiple sessions to obtain more representative results.